Pengaruh Brand Image Dan Harga Terhadap Keputusan Pembelian Produk Skincare The Originote - Setiyanti, Saharani; Ansori, Mochammad Isa (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Amidst the growing concern for the appearance and health of the skin, the skin care products industry has grown tremendously. These developments create increasingly fierce competition in the skincare industry. A company's ability to offer distinctive and unique products will have an impact on the brand which might give it a chance to outperform the market competition. The purpose of writing this article is to find out the influence of brand image and price on the purchase decision of The Originote products. This article, using qualitative methods with a literature study approach, aims to obtain a description of the factors affecting the results of the variables studied. The process involves collecting, evaluating, and synthesizing information from various sources through Google Scholar and Sinta Kemdikbud against scientific publications, journal articles, books, and other sources relevant to the research subject. The result of this article is 1) Brand Imange influences purchasing decisions, 2) price influences purchasing decisions, and 3) brand image and price influence purchase decisions